2018
DOI: 10.17482/uumfd.487773
|View full text |Cite
|
Sign up to set email alerts
|

Bi̇na Diş Duvarlarinda Yoğuşma Di̇kkate Alinarak Gerekli̇ Yalitim Kalinliğinin Beli̇rlenmesi̇: Bi̇tli̇s İli̇ İçi̇n Örnek Çalişma

Abstract: Öz: Türkiye gibi dış ortam sıcaklıklarının geniş bir aralıkta değişkenlik gösterdiği ülkelerdeki binalarda, kış aylarında ısı kayıplarını, yaz aylarında ise ısı kazançlarını azaltmak için yapılan yalıtım uygulamalarının önemi her geçen gün artmaktadır. Yapılan yalıtım uygulamalarında su buharı hareketlerinin göz önüne alınması yoğuşma riski açısından oldukça önemlidir. Yoğuşma veya terleme olarak adlandırılan bu olay, malzemelerin zarar görmesi, mukavemetin azalması ve toplam ısı transfer katsayısının yükselme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In other words, heating costs calculated with respect to heating degree-days method for poultry farms of Balıkesir province in Turkey by using natural gas, coal, liquefied petroleum gas and fuel oil indicated that the lowest fuel costs were obtained with natural gas, while the application of two different cost approaches known as simple payback method and life-cycle cost analysis to the heating degree-days method exhibited that life-cycle cost analysis gave better result in the calculation of optimum insulation thickness of extruded polystyrene used as an insulation material for Bursa city in Turkey [17,18].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, heating costs calculated with respect to heating degree-days method for poultry farms of Balıkesir province in Turkey by using natural gas, coal, liquefied petroleum gas and fuel oil indicated that the lowest fuel costs were obtained with natural gas, while the application of two different cost approaches known as simple payback method and life-cycle cost analysis to the heating degree-days method exhibited that life-cycle cost analysis gave better result in the calculation of optimum insulation thickness of extruded polystyrene used as an insulation material for Bursa city in Turkey [17,18].…”
Section: State Of the Artmentioning
confidence: 99%
“…Calculations were made for Bursa city in Turkey by applying two different cost approaches as the simple payback method without considering inflation and interest rates and life-cycle cost analysis. As a result of this, the optimum insulation thickness was determined as 0.0689 m and 0.0558 m for simple payback method and life-cycle cost analysis giving more reliable and realistic results, respectively [18].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, which is called condensation or sweating, causes undesirable outcomes such as damage to the materials, reduced intensity levels and increased heat losses due to the increased overall heat transfer coefficient. Condensation occurs due to a lack of insulation or insufficient insulation [28][29][30][31][32][33]. The condensation and evaporation amount of building materials according to the climatic zones are presented in Figures 14-25.…”
Section: Condensation and Evaporation Amounts In Building Elementsmentioning
confidence: 99%
“…Bademlioğlu ve ark. İse Bitlis için optimum yalıtım kanlığını yoğuşma durumunu dikkate alarak şubat ayı için hesaplamışlar ve yalıtım kalınlığının en az 0,104 m olması gerektiğini ifade etmişlerdir [8]. Canbolat ve ark.…”
Section: Introductionunclassified